PRE-PRODUCTIONAL DESIGN OF MUNTOCK WHITE PEPPER (PIPER NIGRUM L.) : EFFECTIVENESS OF BAKED SODA (NAHCO3) AND BELT LIME (CA(OH)2), SOAKING TECHNIQUES, AND DIFFERENT CONCENTRATION ON THE QUALITY OF MUNTOCK WHITE PEPPER (PIPER NIGRUM L.) - Qolbu S.M, Aghniya
Pepper is a plantation commodity that is now widely used for medicine and food seasoning throughout the world. Indonesia is the 3rd international pepper producer and contributes 12% of national GDP. Pepper production in Indonesia is estimated to have increased by 0.55% per year since 2019. In 2023, pepper production is estimated at 83.70 thousand tons and is expected to continue to increase until it reaches 84.44 thousand tons in 2026. The increase in production has not yet certainly increases the value of pepper products. This is due to the low quality of the pepper which is in Grade C or Grade 3 due to traditional processing. Traditional processes that do not have safety standards consisting of washing, soaking, peeling, filtering, drying, and packaging mostly result in microbial contamination, oxidation to brownish, high kamba density, incomplete roundness, and hollowness. This research aims to determine the effect of various soaking techniques, additional compounds in soaking, and the concentration of additional compounds on the quality of white pepper. The experimental design used was RALF or a completely randomized factorial design with 8 treatments and 3 repetitions. This factorial takes the form of soaking technique (immersion temperature 25oC and steam 120oC), additional compounds (whiting and baking soda), and concentration (1% and 3%) with each factorial using 2 levels. The quality parameters of white pepper tested were water content, kamba density, color, number of fungal and bacterial microbes, and piperine content. Next, data processing used ANOVA by SPSS version 16.0 which was then continued with the BNT test manually with Excel. From the research results, it was found that treatment with the addition of additional ingredients, soaking techniques, and concentration had significantly different effects on water content, kamba density, color, and number of microbes. The indicators that most determine pepper on the export market are color, microbes and piperine. Based on all the quality parameter test results, it can be concluded that the best treatment is soaking in 3% baking soda (treatment 7). Treatment 7 gave good results in terms of color, microbial growth and piperine. Steam treatment with 1% baking soda in treatment 8 gave a bad effect with a lot of ash from Na which was seen from the high density of kamba. Meanwhile, steam treatment with 1% whiting in treatment 4 had high water content which resulted in easy contamination by coliforms and mold.